The Discursive Construction of Innovation Policy in Peripheralising Estonia - Sebastian Schulz (European Spatial Research and Policy, 2017)
An innovation-driven agenda in regional development policy has emerged in the European Union against the backdrop of peripheralisation, especially in Central and Eastern Europe. Using a discursive analytical framework, the article investigates the ways in which peripheralisation is manifested through language, practices and power-rationalities in Estonian innovation policy discourse. The analysis is footed on key strategic policy documents and semistructured expert interviews. Findings suggest that Estonian innovation policy’s main narrative of the ‘knowledge-based economy’ accepts growing disparities on sub-national level in order to overcome peripherality at European scale and narrows the range of policy solutions perceived as suitable.